Synthesis, structural elucidation, DFT calculation, biological studies and DNA interaction of some aryl hydrazone Cr3+, Fe3+, and Cu2+ chelates - Abu-Dief, Ahmed M.; El-Khatib, Rafat M.; Aljohani, Faizah S.; Al-Abdulkarim, Hessah A.; Alzahrani, Seraj; El-Sarrag, Gehad; Ismael, Mohamed (Computational biology and chemistry, 2022)
The current research focuses on the treatment of Cr(III), Fe(III) and Cu(II) metal ions with aryl hydrazone ligand named (E)-4-(((diphenylmethylene)hydrazono)methyl)benzene-1,3-diol (DPHB) to afford four novel solid complexes with high yields. Different characterization approaches, including infrared, UV–visible, and NMR spectroscopies, elemental analyses, and thermal gravimetric analysis (TGA), revealed that all mononuclear crystalline metal chelates with good thermal stability had a six-coordination with octahedral geometry. Density Functional Theory (DFT) computations were used and provided a reasonable explanation for these metal chelates' electrical and structural features. Furthermore, investigations of electronic absorption spectroscopy, hydrodynamics, and electrophoresis demonstrated that these new compounds interact with calf thymus deoxyribonucleic acid (CT-DNA) in a variety of ways. As a result, the Kb and ∆Gb≠ values of such interactions were in the following order: DPHBCu > DPHBCr > DPHBFe complex. Additionally, the novel metal chelates have been studied anti-bathogenically and found to be significantly effective compared to the comparable DPHB hydrazone ligand. The anti-proliferative activities of the investigated compounds were also evaluated against different lines of cancer cells and exhibited significant cytotoxic activity. In addition, observations of antioxidant activity suggest that antioxidant activity relative to ordinary ascorbic acid was demonstrated in the molecule. [Display omitted] •Some new hydazone metal chelates were synthesized and characterized.•Antimicrobial activities of the investigated compounds were screened.•Interaction of the hydazone metal chelates with DNA was investigated.•Antioxidant and Anticancer activities of the prepared compounds were checked.•Molecular Docking studies were employed to confirm the biological activity.